The Dynamic of ASEAN Tourism Development Within The Travel & Tourism Competitiveness Index / Travel & Tourism Development Index ( TTCI-TTD) Throughout 2017-2023 - Usmar Salam (SOSIO DIALEKTIKA, 2024)
There are numerous researches regarding Tourism in the ASEAN region which generally merely observe the progress of tourism in this region based on the number of foreign tourist visits and foreign exchange income received by ASEAN countries that develop outbound tourism. Dissimilar to other research, this research seeks to observe the development of tourism from the perspectives of the Travel and Tourism Competitiveness Index (TTCI) and the Travel and Tourism Development Index (TTDI), which are immensely focused on featuring the competition/development of tourism from various aspects. By utilizing TTCI / TTDI, the advantages and disadvantages of several aspects in the development of tourism will be essentially visible. Thus, this research shall examine more deeply on the dynamics of ASEAN tourism, focusing more on countries such as Indonesia, Malaysia, Singapore and Vietnam and Thailand from several pillars established by the World Economic Forum (WEF) which are issued every two years. This research focuses on the 2017-2022 period as it would be able to answer the ASEAN tourism competition/development index for the five years, as in such five years span the world of international tourism collapsed due to COVID 19 in 2020-2021.Through this research, it was found that the dynamics of ASEAN tourism development during this period was significantly high, meaning that there were ASEAN countries that experienced declines and increases when viewed from the TTCI/TTDI, and there were countries experiencing stable dynamics. The main key to the success of a country in ASEAN in achieving tourism development lies in the government's ability to manage tourism with its stakeholders and is supported by the domestic political stability of each country.